July 15: Political Economy of a Foiled Coup - (:unkn) unknown (SETA FOUNDATION, 2016)
Turkey has suffered from interventions and enforcements against its elected governments, on the average, in every decade. Against this background, this study presents an assessment of the political economy of the foiled coup attempt on July 15, 2016 via the main theoretical approaches developed to explain the relations between economy and military coups. In this context, the study looks at the economic background of the pre-coup attempt period, crises scenarios serviced by international institutions and the goals of the perception management orchestrated by the western world for the attempted coup. In the same breath, the study presents in detail the FETO's colossal economic power amounting to billions of dollars. The main conclusion is that the July 15 coup attempt was perpetrated to prevent an interruption in flow of financial resources into a murky network of business enterprises around a messianic cult.